Input Data as used in Kreuzer et al., Geoscientific Model Development publication (doi 10.5194/gmd-14-3697-2021) - Kreuzer, Moritz (Zenodo, 2021)
Input data for the PISM-MOM coupling framework as used in the Geoscientifc Model Development publication "Coupling framework (1.0) for the PISM (1.1.4) ice sheet model and the MOM5 (5.1.0) ocean model via the PICO ice shelf cavity model in an Antarctic domain" by Moritz Kreuzer, Ronja Reese, Willem Huiskamp, Stefan Petri, Torsten Albrecht, Georg Feulner and Ricarda Winkelmann. : {"references": ["Le Brocq, A. M., Payne, A. J., and Vieli, A.: An improved Antarctic dataset for high resolution numerical ice sheet models (ALBMAP v1), Earth Syst. Sci. Data, 2, 247\u2013260, https://doi.org/10.5194/essd-2-247-2010, 2010.", "Fretwell et al.: Bedmap2: improved ice bed, surface and thickness datasets for Antarctica, The Cryosphere, 7, 375\u2013393, https://doi.org/10.5194/tc-7-375-2013, 2013.", "Schmidtko, S., Heywood, K. J., Thompson, A. F. and Aoki, S.: Multidecadal warming of Antarctic waters, Science, 346 (6214), 1227-1231, https://doi.org/10.1126/science.1256117, 2014.", "van Wessem et al.: Modelling the climate and surface mass balance of polar ice sheets using RACMO2 \u2013 Part 2: Antarctica (1979\u20132016), The Cryosphere, 12, 1479\u20131498, https://doi.org/10.5194/tc-12-1479-2018, 2018."]}